Risiko Kredit Perumahan dengan Skema Fasilitas Likuiditas Pembiayaan Perumahan (Studi Kasus Bank BTN Pusat, Jakarta) (Credit Risk of Housing Finance with the Scheme of Liquidity Facility of Housing Finance (Case Study of Bank BTN Pusat, Jakarta)) - Asep Rakhmat; Musa Hubeis; Tb. Nur Ahmad Maulana (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2014)
The purpose of this study is to analyze the credit risk of housing finance with the scheme of Liquidity Facility of Housing Finance and to find out the management and control of the credit risk of housing finance with the scheme of FLPP at Bank BTN. Credit risk measurement uses the Credit Risk+ method and obtains the alternative of credit risk control strategy using the Analytical Hierarchy Process(AHP). The result of calculation of the credit risk with the Credit Risk+ method shows the value of VaR for March 2013 of Rp 2,450 million or 9.38% of the total credit and it is based on the testing of the validity with the back testing method and the calculation of potential losses with the method of Credit Risk+ portfolio resulting the deviation of 5.27%. This shows that the method is in accord with the measuring of the potential loss of the credit risk of housing finance with the scheme of FLPP BTN in March 2013. The alternative strategies becoming the priority in controlling the credit risk of housing finance of the scheme of FLPP at Bank BTN are to tighten the character assessment of borrowers with the weight of 0.3547 and to give the intensive training about the eligibility analysis of borrowers to the Account Officers (AO) and Marketers in order to be more ready and competent in facing the increase of the filing of financing with the value of 0.2808. The study result shows that most involved actor and having the effect in controlling the credit risk of housing finance with the scheme of FLPP is AO with the weight of 0.2734, while the purpose is becoming the main priority in controlling the credit risk of housing finance of FLPP scheme and it is the eligibility of prospective borrower with the weight of 0.3716.Keywords : credit risk, controlling risk strategy, FLPP